Folate, alcohol, ADH1B and ALDH2 and colorectal cancer risk. Issue 4 (30th March 2021) - Seol, Ju Eun; Kim, Jeongseon; Lee, Bong-Hwa; Hwang, Dae-Yong; Jeong, Jinyoung; Lee, Hun-Jae; Ahn, Yoon-Ok; Lee, Jung Eun; Kim, Dong-Hyun
Abstract: Objective: There is limited evidence on the interaction by alcohol dehydrogenase 2 ( ADH1B ) (rs1229984) and aldehyde dehydrogenase 2 ( ALDH2 ) (rs671) regarding the associations of alcohol and a methyl diet (low folate and high alcohol intake) with cancer risk, partly because of rare polymorphisms in Western populations. Design: In a case–control study, we estimated the ORs and 95 % CIs to evaluate the associations of ADH1B and ALDH2 genotypes with colorectal cancer (CRC) and the joint association between methyl diets and ADH1B and ALDH2 polymorphisms with CRC risk using logistic regression models. Setting: A hospital-based case–control study. Participants: In total, 1001 CRC cases and 899 cancer-free controls admitted to two university hospitals. Results: We found that alcohol intake increased the risk of CRC; OR (95 % CI) was 2·02 (1·41, 2·87) for ≥60 g/d drinkers compared with non-drinkers ( P trend < 0·001). The associations for two polymorphisms with CRC were not statistically significant. However, we found a potential interaction of ALDH2 with methyl diets and CRC. We observed a 9·08-fold (95 % CI 1·93, 42·60) higher risk of CRC for low-methyl diets compared with high-methyl diets among individuals with an A allele of ALDH2, but the association was not apparent among those with ALDH2 GG ( P interaction = 0·02). Conclusions: Our data support the evidence that gene–methyl diet interactions may be involved in CRC risk in East Asian populations, showing that a low-methyl diet increased the risk of CRC among individuals with an A allele of ALDH2 .